O‘QUV TOPSHIRIQLARINI VAZIFASIGA KO‘RA TASNIFLASH VA BLUM TAKSANOMIYASINING AHAMIYATI - Hamroyev, G‘.H. (SCIENCE and SOCIETY, 2020)
The article explains the classification of learning tasks according to the tasks they perform during the lesson, the description of each type, and their application. Samples of assignments are provided, and are divided into learning tasks that develop and test knowledge, skills, and competencies. This reveals the significance of Bloom's taxonomy.
Keywords: assignment; types of assignments; developmental assignments; test assignments; knowledge; skills and competencies; Bloom's taxonomy; comprehension; application; analysis; evaluation